A LEADER-megközelítés helye és szerepe a vidékfejlesztési politika megvalósításában - Kis, Krisztián; Szekeresné Köteles, Rita (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The LEADER approach as a sustainable development streamline based on local resources, means a paradigm of competitive and sustainable rural development. The Local Action Groups (LAGs) as local development organizations forming in the framework for applying the concept of LEADER method, have an important role in realization of objectives of the rural development policy at local level. The execution of the rural development policy can be interpreted as the fulfillment of levels building on each other in an objectiveinstrument type of implementation, which is pervaded by the LEADER approach. The LEADER is not only a successful way of rural development, but a concept or a model that pervades and embraces the whole process of programming and execution of rural development from the policy level to the implementation of projects.